The Effect of Good Corporate Governance on The Financial Performance of Banks Listed on The Indonesia Stock Exchange - Anggun Tiara Kasih; Isnurhadi; Marlina Widiyanti (CV. Syntax Corporation Indonesia, 2024)
The purpose of this study is to obtain empirical evidence of the, Managerial's Ownership, Institutional Ownership, independent board of commissioners, board of directors, and audit committee on the Banking Company firm's performance listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling, the research samples obtained totaled 6 companies with a research period from 2018-2022 so that there were 30 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is multiple regression analysis method. The results showed that Managerial's Ownership and Audit Committee has a significant positive effect, Institutional Ownership, independent board of commissioners, board of directors has no effect on firm's perfromance. The implication of this research is that companies must pay attention to that Managerial's Ownership and Audit Committee and those that can affect profitabilty so that company performance can increase.